Linearization by means of Linear Implicit Rectangular Descriptions (2017)
This paper discusses a novel implementable approach to an exact linearization procedure based on the implicit systems techniques. The formal procedure we propose includes a specific “splitting” of the nonlinear state representation in two parts that involve a basic rectangular representation and an auxiliary nonlinear algebraic equation. The proposed linear implicit systems description makes it possible to apply the conventional linear control techniques to an initially given sophisticated nonlinear dynamic model. © 2017